For Latinx, by Latinx: Race-conscious leadership in policy implementation - Felix, Eric R. (Education Policy Analysis Archives, 2021)
Policy implementation research tends to document the failures of reform, describing the myriad ways implementers miss the mark in translating intent into impact; or in the words of Derrick Bell, policy scholars are left with examining the “unfilled hopes of racial reform” (2004, p. 185). In contrast, this article presents an intrinsic case study where campus leaders took a race-conscious approach to implementing a state-wide reform known as the Student Equity Policy. I constructed the TrenzaPolicy Implementation Framework to center the experience, knowledge, and assets of Latinx leaders in community college that oversee and implement policy reform. The framework highlights the raced-gendered perspectives of Latinx leaders in community college to understand their motivations to implement policy in race-conscious ways (Delgado Bernal, 2002). I conducted in-depth and sustained fieldwork to learn how implementers understood and responded to state-level reform in race-conscious ways and used the policy to target and address one of the most pressing issues in higher education, the inequitable rates of transfer for Latinx students. I share how the salience of racialized-gendered identity, cultural intuition, social context, and enacting agency allowed leaders to envision more race-conscious possibilities for policy reform and its implementation on campus.